The Lure of Illustration in the Nineteenth Century
XVII, 279 p.
Keywords: This volume tackles the subject of illustration, technically, metaphorically and historically in nineteenth-century periodicals, displaying the ubiquity of the visual in the press: the articles cover material illustration, graphics, and design and metaphorical use of images in the letterpress, offering specific examples and theoretical approaches.